Cholecystokinin octapeptide improves hippocampal glutamatergic synaptogenesis and postoperative cognition by inhibiting induction of A1 reactive astrocytes in aged mice. (17th August 2021) - Chen, Lei; Yang, Ning; Li, Yue; Li, Yitong; Hong, Jingshu; Wang, Qian; Liu, Kaixi; Han, Dengyang; Han, Yongzheng; Mi, Xinning; Shi, Chengmei; Zhou, Ying; et al.
Abstract: Aims: Delayed neurocognitive recovery (dNCR) is a common postoperative complication in geriatric surgical patients for which there is no efficacious therapy. Cholecystokinin octapeptide (CCK‐8), an immunomodulatory peptide, regulates memory and learning. Here, we explored the effects and mechanism of action of CCK‐8 on dNCR. Methods: We applied laparotomy to establish a model of dNCR in aged mice. Morris water maze and fear conditioning tests were used to evaluate cognition. Immunofluorescence was used to detect the density of CCK‐8, A1 reactive astrocytes, glutamatergic synapses, and activation of microglia in the hippocampus. Quantitative PCR was performed to determine mRNA levels of synapse‐associated factors. A1 reactive astrocytes, activated microglia, and glutamatergic synapse‐associated protein levels in the hippocampus were assessed by western blotting. Results: Administration of CCK‐8 suppressed the activation of microglia, the induction of A1 reactive astrocytes, and the expression of tumor necrosis factor alpha, complement 1q, and interleukin 1 alpha in the hippocampus. Furthermore, it promoted glutamatergic synaptogenesis and neurocognitive recovery in aged dNCR model mice. Conclusion: Our findings indicated that CCK‐8 alleviated cognitive impairment and promoted glutamatergic synaptogenesis by inhibiting the induction of A1 reactive astrocytes and the activation of microglia. CCK‐8 is, therefore, a potential therapeutic target for dNCR. Abstract : Cholecystokinin octapeptide (CCK‐8) alleviated cognitive impairment and promoted glutamatergic synaptogenesis by inhibiting the induction of A1 reactive astrocytes, which was induced by activated microglia‐released tumor necrosis factor alpha (TNF‐α), complement component 1, q subcomponent (C1q) and interleukin 1 alpha (IL‐1α). These findings demonstrated that CCK‐8 is a potential therapeutic target for delayed neurocognitive recovery (dNCR).